1998
DOI: 10.1096/fasebj.12.9.747
|View full text |Cite
|
Sign up to set email alerts
|

High expression of leptin by human bone marrow adipocytes in primary culture

Abstract: Adipocytes participate in the microenvironment of the bone marrow (BM), but their exact role remains to be determined. It has recently been shown that leptin, a hormone secreted from extramedullary adipocytes, could be involved in hematopoiesis. Therefore we have developed a primary culture system of human BM adipocytes to characterize their differentiation and determine whether leptin is also secreted from these adipocytes. BM cells were cultured with fetal calf and horse sera. In the presence of dexamethason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(111 citation statements)
references
References 38 publications
7
98
0
6
Order By: Relevance
“…Conversely, it is known that adipocytes participate in the microenvironment of the bone marrow and that these adipocytes are a secondary source of leptin production (20). Thomas et al (14) recently demonstrated a direct osteogenic effect of leptin on a human marrow stromal cell line with the capability to differentiate to either osteoblasts or adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it is known that adipocytes participate in the microenvironment of the bone marrow and that these adipocytes are a secondary source of leptin production (20). Thomas et al (14) recently demonstrated a direct osteogenic effect of leptin on a human marrow stromal cell line with the capability to differentiate to either osteoblasts or adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Limit of detection for the assay was 0.2 ngaml. 14 Pearson's correlation coef®cient r was used to evaluate associations between BM and plasma leptin. Student's t-test was used for statistical signi®cance.…”
Section: Leptin Determinationsmentioning
confidence: 99%
“…1 Adipocytes are abundant in the bone marrow (BM) microenvironment and might be responsible for the high concentration of leptin in BM. 2 The leptin receptor (OB-R) has recently been detected on human hematopoietic progenitor cells expressing the CD34 antigen, and leptin was reported to induce proliferation and differentiation in these cells. 3,4 Multiple isoforms of OB-R have been identified, including a long isoform and several isoforms with short cytoplasmic domains.…”
mentioning
confidence: 99%